1975
DOI: 10.1099/0022-1317-28-2-225
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodification and the Expression of Virulence in Mice by Defined Strains of Semliki Forest Virus: the Effects of Cyclophosphamide

Abstract: SUMMARYMice were infected i.c. or i.p. by an avirulent clone of Semliki Forest virus at various times before or after the i.p. administration of a single dose of cyclophosphamide. Consequent changes in the patterns of viraemia and antibody production are interpreted in terms of the potentiation of the initial infection or the decreased resistance to subsequent lethal challenge.These changes demonstrate two distinct modes of immunomodification determined by the time of cyclophosphamide administration in relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
(8 reference statements)
1
14
0
Order By: Relevance
“…These were as in the previous paper (Bradish et al 1975) and earlier reports (Bradish, Allner & Maber, 1971). Most experiments were with the avirulent strain A7.CI or its derived clone A7(74).CI which efficiently immunize young mature mice (~ IOO p.f.u./i.p.…”
Section: Strains Of Semliki Forest Virus (Sfv)mentioning
confidence: 81%
See 2 more Smart Citations
“…These were as in the previous paper (Bradish et al 1975) and earlier reports (Bradish, Allner & Maber, 1971). Most experiments were with the avirulent strain A7.CI or its derived clone A7(74).CI which efficiently immunize young mature mice (~ IOO p.f.u./i.p.…”
Section: Strains Of Semliki Forest Virus (Sfv)mentioning
confidence: 81%
“…A differentially greater sensitivity of T cells than B cells to the action of 1-asparaginase has been reported by Berenbaum,Cope & Jeffrey (I973). If, as these authors suggest, B cells enjoy a partially protective micro-environment, then this is evidently less effective against the action of cyclophosphamide which (Table 4 and Bradish et al 1975) influences antibody memory and the development of protection against challenge (secondary potentiation) to an extent not observed with 1-asparaginase.…”
Section: Summary Of Influences Of Immunomodifications Upon the Efficimentioning
confidence: 99%
See 1 more Smart Citation
“…Aurothiolates are linear, 2-coordinate complexes in which two ligands are covalently bound on either side of a gold nucleus in a +1 oxidation state (gold (I)). Early studies suggested these gold compound affected the outcome of SFV infection by an effect on macrophages (Allner et al, 1974;Bradish et al, 1975). Subsequent studies con®rmed that these compound have an effect on macrophages Webb, 1982, 1990) but suggested that this was not the basis for their effect on the course of SFV infection (Mehta and Webb, 1987;.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that treatment of 3 ± 4-week-old mice with the gold compound sodium aurothiomalate (GSTM) prior to inoculation with A7(74) renders this infection lethal (Allner et al, 1974;Bradish et al, 1975;Pathak and Webb, 1983;Mehta and Webb, 1982, Gates et al, 1984Mehta et al, 1987. GSTM is an aurothiolate compound which has been used in the treatment of rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%